OPTIMIZATION OF THE USE OF FLY ASH AS AN ADDITIVE PORTLAND COMPOSITE CEMENT (PCC) - Leni Rumiyanti; Listiani Listiani; Tika Damayanti (Program Studi Fisika Universitas Negeri Jakarta, 2019)
Research has been carried out on the optimization of the use of Lahat Fly Ash as an Additive Portland Composite Cement (PCC) which aims to determine the optimum conditions for adding Lahat fly ash to produce cement with physical and chemical requirements in accordance with SNI 7064:2014 and discover the ideal composition of cement with fly additions Lahat ash from various cement compositions. The quality analysis in making PCC cement is chemically in the form of Insoluble Residue (IR), Loss of Ignition (LOI), and free lime (FCaO) as well as the quality of physics in the form of Blaine, setting time, and cement mortar compressive strength. The results obtained after the process of making PCC cement with the addition of 14% Lahat fly ash, namely PCC cement in optimum conditions with physical and chemical requirements in accordance with SNI 7064: 2014 where the ideal composition of PCC cement manufacture is 14% Lahat fly ash, clinker 62%, 3% gypsum, 18% limestone, and 3% pozzolans in making PCC cement. Therefore, Lahat fly ash can be used as an alternative mixture in making PCC cement.